Analisa Rasio Keuangan untuk Menilai Tingkat Kesehatan Perusahaan pada PT. Pegadaian Kanwil VII Denpasar - Ni Putu Puspa Jayanti; Ni Wayan Suartini; Ni Putu Andini Desiyanti Laksmi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
With the use of financial analysis as a gauge for the company's financial health, this research seeks to analyze PT. Pegadaian's performance. With an emphasis on financial analysis, including liquidity, solvability, profitability, and efficiency, the study employs descriptive analysis. According to the findings, PT. Pegadaian has demonstrated strong financial performance, with its liquidity allowing for efficient risk management. Efficiency shows how well a business uses its resources to generate revenue, whereas profitability ratio shows how well it generates profits. The report stresses how crucial it is to routinely assess financial performance in order to keep the company's standing and avoid market fluctuations. The organization must adjust to boost operational efficiency and enhance community service delivery in light of technology improvements and digitalization.